Family occurrence of achalasia and diffuse spasm of the oesophagus. Issue 11 (November 1988) - Frieling, T; Berges, W; Borchard, F; Lübke, H J; Enck, P; Wienbeck, M
Abstract : In view of the unknown aetiology of achalasia and diffuse oesophageal spasm we report four families (father/son, mother/son, brother/brother, cousin/cousin) with achalasia and oesophageal spasm examined by radiology, endoscopy and manometry. Family occurrence of oesophageal motor disorders supports the hypothesis that a genetic trait may play a role in the pathogenesis. The family coincidence of achalasia and oesophageal spasm supports a close relationship between the two diseases.